Heme oxygenase‐2 deletion impairs macrophage function: implication in wound healing. Issue 1 (23rd October 2014) - Bellner, Lars; Marrazzo, Giuseppina; van Rooijen, Nico; Dunn, Michael W.; Abraham, Nader G.; Schwartzman, Michal L.
Abstract : Heme oxygenase (HO)‐2 deficiency impairs wound healing and exacerbates inflammation following injury. We examine the impact of HO‐2 deficiency on macrophage function and the contribution of macrophage HO‐2 to inflammatory and repair responses to injury. Corneal epithelial debridement was performed in control and macrophage‐depleted HO‐2 ‐/‐ and wild‐type (WT) mice and in bone marrow chimeras. Peritoneal macrophages were collected for determination of phagocytic activity and classically activated macrophage (M1)‐alternatively activated macrophage (M2) polarization. Depletion of macrophages delayed corneal healing (13.2%) and increased neutrophil infiltration (54.1%) by day 4 in WT mice, whereas in HO‐2 ‐/‐ mice, it did not worsen the already impaired wound healing and exacerbated inflammation. HO‐2 ‐/‐ macrophages displayed an altered M1 phenotype with no significant expression of M2 or M2‐like activated cells and a 31.3% reduction in phagocytic capacity that was restored by inducing HO‐1 activity or supplementing biliverdin. Macrophage depletion had no effect, whereas adoptive transfer of WT bone marrow improved wound healing (34% on day 4) but did not resolve the exaggerated inflammatory response in HO‐2 ‐/‐ mice. These findings indicate that HO‐2‐deficient macrophages are dysfunctional and that macrophage HO‐2 is required for proper macrophage function but is insufficient to correct the impaired healing of the HO‐2 ‐/‐ cornea, suggesting that corneal epithelial expression of HO‐2 is a key to resolution and repair in wound healing.—Bellner, L., Marrazzo, G., van Rooijen, N., Dunn, M. W., Abraham, N. G., Schwartzman, M. L., Heme oxygenase‐2 deletion impairs macrophage function: implication in wound healing. FASEB J. 29, 105–115 (2015). www.fasebj.org